2020
DOI: 10.48550/arxiv.2012.07593
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-testing of binary Pauli measurements requiring neither entanglement nor any dimensional restriction

Ananda G. Maity,
Shiladitya Mal,
Chellasamy Jebarathinam
et al.

Abstract: Characterization of quantum devices received from unknown providers is a significant primary task for any quantum information processing protocol. Self-testing protocols are designed for this purpose of certifying quantum components from the observed statistics under a set of minimal assumptions. Here we propose a selftesting protocol for certifying binary Pauli measurements employing the violation of a Leggett-Garg inequality. The scenario based on temporal correlations does not require entanglement, a costly… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…An immediate one, is the experimental tests of the systems identified that violate MR but satisfy the LGIs. A broader extension, is the refinement of the different protocols for detecting quantum behaviour, such as protocols for certifying quantum components uniquely and device-independently [49][50][51], to be robust against case where the LGIs are satisfied but MR is still violate. A third extension of this work is identifying the relationship between the different MR conditions which have been discovered over the past decade (those explored in this paper [17][18][19][24][25][26][27] as well as others [52,53]).…”
Section: Discussionmentioning
confidence: 99%
“…An immediate one, is the experimental tests of the systems identified that violate MR but satisfy the LGIs. A broader extension, is the refinement of the different protocols for detecting quantum behaviour, such as protocols for certifying quantum components uniquely and device-independently [49][50][51], to be robust against case where the LGIs are satisfied but MR is still violate. A third extension of this work is identifying the relationship between the different MR conditions which have been discovered over the past decade (those explored in this paper [17][18][19][24][25][26][27] as well as others [52,53]).…”
Section: Discussionmentioning
confidence: 99%